Proportion and factors associated with covid-19 reinfection among Universiti Sains Malaysia health campus residents - Basri, Ijlal Syamim Mohd (2023)
Background: COVID-19 will remain an endemic disease worldwide, and reinfection is possible. This phenomenon can be attributed to the highly mutable nature of COVID-19, which gives rise to new variants that exhibit increased transmission and immune evasion. Universiti Sains Malaysia (USM) Health Campus is a unique population as the campus has a higher-risk population due to the presence of a health center where the risk of COVID-19 exposure is the highest among the clinical staff. The risk is also shared among clinical health students who reside in student residences and risk exposing other residences. Identifying people at risk will help us in better prevention and control of the disease. Objective: This study aimed to describe the proportion of COVID-19 reinfection among USM Health Campus residents and to determine the factors associated with COVID-19 reinfection among USM Health Campus residents for the years 2021 and 2022. Methodology: This was a retrospective record review using secondary data year 2021 and 2022 from COVID-19 diseases outbreak and management data in USM Health Campus. The study was conducted from November 2022 till April 2023. Relevant data were extracted from the secured EXCEL sheet. The data were collected using proforma and were analyzed using SPSS version 26. The data were analyzed using descriptive analysis, as well as simple and multiple logistic regression. Result: A total of 137 cases out of 3469 COVID-19 positive cases were included in this study in which the proportion of COVID-19 reinfection cases were 3.95%. The associated factors for COVID-19 reinfection that were found to be significant were age group >40 years old, adjOR = 0.265 (95% CI: 0.15,0.47, p-value <0.001), vaccination status, adjOR = 0.254 (95% CI: 0.15,0.43, p-value <0.001), and workplace transmission adjOR = 1.815 (95% CI: 1.06,3.10, p-value = 0.003). Conclusions: COVID-19 reinfections were uncommon on USM Health Campus. Age group >40 years old, vaccination status and workplace transmission were the factors associated with COVID-19 reinfection among USM Health Campus residents. Screening targeted young age group should be enhanced and greater emphasis on health promotion and awareness in workplace for prevention and control of COVID-19 reinfection.